2018
DOI: 10.1016/j.jad.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Mood instability as a predictor of clinical and functional outcomes in adolescents with bipolar I and bipolar II disorder

Abstract: MI differs by diagnostic subtype, is relatively stable over time, and predicts clinical and functional outcomes. Targeting MI should be considered a clinical focus to augment traditional methods of assessing and treating BD during adolescence to enhance clinical and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
(58 reference statements)
2
37
0
Order By: Relevance
“…As a result, delays of several years can occur between an initial diagnosis of a mental disorder and a diagnosis of BD [96]. BD patients can also experience intense, rapidly shifting emotional states [120], with BD patients experiencing a greater number of mood swings than others impacting on their functioning [121]. Co-morbidity with other psychiatric disorders is also common making treatment complex [69].…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…As a result, delays of several years can occur between an initial diagnosis of a mental disorder and a diagnosis of BD [96]. BD patients can also experience intense, rapidly shifting emotional states [120], with BD patients experiencing a greater number of mood swings than others impacting on their functioning [121]. Co-morbidity with other psychiatric disorders is also common making treatment complex [69].…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…Here, AL belongs to a constellation of symptoms preceding the development of the disorder [18], is present early in the course of illness [19], in manic and mixed episodes [20], but also in periods of euthymia [21]. Hence, AL appears to be both a trait-and state-dependent factor that is associated with poor prognostic outcomes [21,22]. Our research group has previously found relationships between elevated AL and clinical correlates such as AUD, childhood trauma, suicidality, mixed episodes and anxiety, as well as intact executive functioning in BD [7,19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of mood is a central core feature of BD. Many patients with BD experience subsyndromal mood swings on a daily basis that are associated with increased risk of relapse and hospitalization [12][13][14]. Our group has in recent studies showed that smartphone-based daily self-monitored mood alterations are associated with increased perceived stress and decreased quality of life and functioning [15,16] and that increased mood instability may behave as a genetic vulnerability trait for BD being present in remitted BD patients [15] and in their unaffected relatives (UR) [16].…”
Section: Introductionmentioning
confidence: 99%